Comparison of postoperative muscle strength and ambulation ability between two different concentrations of bupivacaine in patients undergoing gynecologic oncology surgery under combined general-epidural anesthesia: A double blinded, randomized-controlled study - Tirasuntornwong, Viranut; Plerksophon, Lalita; Saengthong, Narunlak (Journal of Medicine and Health Sciences, 2023)
Gynecologic oncology operations constitute major surgery. Optimizing pain management and enhancing patient recovery with early ambulation can reduce postoperative complications. Epidural analgesia is a good technique to control pain; however, it can have some side effects. One of the most common side effects is lower motor weakness, which can impede early ambulation. The primary outcome of this double-blinded, randomized controlled study was to compare muscle strength, and secondary outcomes were to study the ability to ambulate, pain score, and complications between two concentrations of bupivacaine. One hundred and ten patients ASA I-II who underwent surgery and received epidural analgesia were included and randomly assigned to two groups. Patients in group A were treated with 0.1% bupivacaine plus fentanyl 2 mcg/ml. Patients in group B received 0.0625% bupivacaine plus fentanyl 2 mcg/ml. At 24 and 48 hours postoperatively, muscle strength, ambulation ability, pain score, and complications were compared. The results indicated that muscle strength, as assessed using the Modified Bromage scale measurement, showed no statistical difference between the two groups. Furthermore, there was no statistical significance in ambulation ability between both groups (at 24 hours, group A=52.9% vs group B=68.8% (p=0.110) and at 48 hours, group A=92% vs group B=94% (p=0.679)). Additionally, the pain score, incidence of hypotension, nausea, vomiting, and itching results were also not significantly different. In conclusion, both concentrations of bupivacaine had comparable characteristics of pain management in terms of muscle strength, ambulation ability, pain score, and side effects. Therefore, 0.0625% bupivacaine plus fentanyl 2 mcg/ml may be used in patients undergoing gynecologic oncology surgery to optimize pain control and promote enhanced patient recovery.